Evidence That Hyaluronidase Is Not Involved in Tissue Invasion of the Protozoan Parasite Entamoeba histolytica - Nickel, Rosa (American Society for Microbiology, 2000)
As previous reports suggested that a hyaluronidase is involved in tissue invasion of Entamoeba histolytica, we searched for such an activity in trophozoite extracts. A hyaluronidase activity was not detectable in long-term cultures or in amoebae freshly passaged through a gerbil liver, as evidenced by four different techniques.